A Predator-Prey Gompertz Model with Time Delay and Impulsive Perturbations on the Prey - Jianwen Jia; Chunhua Li (Discrete Dynamics in Nature and Society)
We introduce and study a Gompertz model with time delay and impulsive perturbations on the prey. By using the discrete dynamical system determined by the stroboscopic map, we obtain the sufficient conditions for the existence and global attractivity of the “predator-extinction” periodic solution. With the theory on the delay functional and impulsive differential equation, we obtain the appropriate condition for the permanence of the system.